New ideas for high performance coaches: A case study of knowledge transfer in sport science - Reade, I.; Rodgers, W.; Spriggs, K. (International Journal of Sports Science and Coaching, 2008)
Research related to how coaches learn concludes that coaches most often learn from other coaches. So far, there has been little evidence to suggest that coaches rely on sport scientists for their information, which would indicate minimal interaction between sport scientists and coaches. The purpose of this study was to determine the type and source of new ideas that high-performance coaches use to understand the extent to which sport science is the source of those ideas. This project utilized a single case study design involving a group of 20 high-performance coaches in 12 different sports in a university environment, which one would expect to be conducive to interaction between sport scientists and coaches. The method included the administration of a questionnaire, followed by a structured personal interview. Our findings suggest that these coaches do believe that sport science can contribute to coaching, are interested in having a sport scientist work with them, and are motivated to find and implement new ideas in their sport programs. Despite this, most of the respondents indicated they usually get those new ideas from other coaches, or from coaching clinics and seminars, and not from sport scientists or their written work. Reasons stated included a lack of time to look for new ideas and hence the use of expedient sources, and a lack of interest in academic publications.